Effectiveness of an Interprofessional Education Module among Health Professions Students: A Pre–Post Evaluation Study - Bianchi, Monica; Soldini, Emiliano; Lisi, Angela; Gradellini, Cinzia (Innovations in Pedagogy and Technology, 2026)
The World Health Organization recommends the implementation of interprofessional healthcare teams to address the increasing complexity of patient populations. Interprofessional Education (IPE) is recognised as a key educational strategy for preparing healthcare professionals to work effectively in such teams, as it is fundamental to the development of collaborative practice and fosters opportunities for mutual understanding, constructive dialogue, and cooperation, with the ultimate aim of delivering high-quality and safe care. This study presents a pre–post evaluation of an IPE course that included an interprofessional collaborative learning unit attended by undergraduate students in Nursing, Occupational Therapy, and Physiotherapy, as well as postgraduate students in Medicine. The impact of the educational intervention was assessed in both the short and long term using the Interprofessional Attitudes Scale (IPAS), which measures attitudes related to the Core Competencies for Interprofessional Collaborative Practice. Data analysis focused on changes across the five IPAS subscales. At post-intervention, the Interprofessional Biases subscale showed the lowest level of agreement (54%). Strong agreement was observed for Teamwork, Roles and Responsibilities (≥75%) and Community-Centredness (≥79%), while extremely high agreement was reported for Diversity and Ethics (94%) and Patient-Centeredness (97%). The IPE intervention demonstrated a positive short-term effect on students’ attitudes towards interprofessional collaboration, particularly in relation to teamwork, professional roles, and the reduction of interprofessional biases. However, these effects were not sustained in the long term. Overall, the findings support existing literature by confirming the short-term impact of IPE on students’ attitudes, perceptions, understanding of professional roles, and recognition of the value of other health professions.